Literasi Keuangan, Risk Tolerance dan Overconfidence Terhadap Keputusan Investasi pada Pekerja di Kawasan Industri Cikarang - Efi Listiani; Erin Soleha (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the effect of financial literacy, risk tolerance and overconfidence on investment decisions for workers in the Cikarang Industrial Area. The research method used is quantitative method with a total sample of 100 respondents which is determined by using non-probability sampling technique. The results of this study show that the t-statistic value for the financial literacy variable is 3.089 > 1.96 and the p-value is 0.002 <0.05. Overconfidence has a t-statistic value of 4.339 > 1.96 and a p-value of 0.000 <0.05 and the risk tolerance variable has a t-statistic value of 0.081 <1.96 and a p-value of 0.935 > 0.05. In conclusion, financial literacy and overconfidence have a significant positive effect on workers' investment decisions in the Cikarang Industrial Area. Meanwhile, risk tolerance has no effect on workers' investment decisions in the Cikarang Industrial Area. The most dominant variable affecting investment decisions is overconfidence so that the higher the level of self-confidence a person will make the decision to invest will increase. Keywords: Overconfidence, Investment Decision, Literacy, Risk Tolerance